Effect of resveratrol on restoring spermatogenesis in experimental cryptorchid mice and analysis of related differentially expressed proteins. (2nd February 2015) - Li, Enzhong; Guo, Yuping; Wang, Gailing; Chen, Fujia; Li, Qingwang
Abstract The present study aimed to evaluate the effect of trans‐Resveratrol on spermatogenesis. Male Kunming suckling mice (10 days old) were surgically rendered cryptorchid and subcutaneously injected with trans‐Resveratrol at doses of 5, 10, 20, and 40 µg/g/day as groups I, II, III, and IV, respectively, for 35 days. Animals in the control group received 10 µL/mouse/day of olive oil. Serum estradiol, testosterone, FSH, and LH levels were measured on day 45. Tissue analysis and sperm morphological abnormalities analysis were done. Results showed that in the control group and group I only spermatogonia and primary spermatocytes were present, whereas spermatogenesis was totally restored in groups II, III, and IV. Sperm counts in groups III and IV were remarkably higher than the control group (P < 0.05). The morphological abnormalities in resveratrol‐treated groups were higher than the mature mice. Serum estradiol levels in the resveratrol‐treated groups were not significantly different from the control group, but were lower than the mature mice (P < 0.05). There was no significant difference in serum testosterone levels between the resveratrol‐treated groups and mature mice, but the levels in the resveratrol‐treated groups was significantly lower than the control group (P < 0.05). No significant influence of trans‐Resveratrol was observed on serum FSH levels in all cryptorchid mice. Serum LH levels in groups I, II, and III were higher than the control group. These results indicate that trans‐Resveratrol restores spermatogenesis in cryptorchid mice. In addition, proteomic analysis between the 20 μg/g/day resveratrol‐treated group and the control group was carried out, and five kinds of proteins (BAF250, ZFP261, CHD1L, RBBP9, and SOHLH2) were identified. The expression of SOHLH2 increased, while that of BAF250, ZFP261, CHD1L, and RBBP9 decreased in the 20 µg/g/day resveratrol‐treated group, indicating that SOHLH2 may contribute to testicular germ cell differentiation.